Implementation of a Collaborative Approach to Improve Teacher Professional Competence at MI Negeri 9 Aceh Besar - Mutiyani; Mansuryadi (Jurnal Cendekia Islam Indonesia, 2025)
This classroom action research aimed to improve teachers’ professional competence through the implementation of a collaborative learning approach at MIN 9 Aceh Besar. The study was conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. Participants included teachers from MIN 9 Aceh Besar during the 2025 academic year. Data were collected using observation, documentation, and interviews, and analyzed through descriptive qualitative techniques. The results indicated a significant increase in teachers’ professional competence, reflected in their improved ability to design lesson plans, manage classrooms, apply innovative learning strategies, and conduct assessments aligned with curriculum standards. In the first cycle, only 68% of the teachers demonstrated competence at the expected level, while in the second cycle, the percentage rose to 87%. These findings suggest that collaborative learning fosters a culture of shared reflection, mutual support, and professional growth among teachers. The study concludes that the collaborative approach effectively enhances teachers’ pedagogical practice and contributes to sustained improvement in instructional quality within Islamic elementary schools.